xxi Century Latin American Journalists: Beyond Post-Truth Politics - Amado, Adriana (2017)
Considering the complexity of circumstances that journalism is facing, academia should rethink the classical conceptions of the profession, especially when they reduce journalism to abstract models disregarding reporters’ actual practices. Results of a global research propose a new definition of journalism, a profession caught between conflicting interests that lack the supremacy of news production, as it used to be in the past century. It is all about broadening the debate to reconsider the role of the journalist in the contemporary information report, beyond current concepts such as post-truth.